Evidence- Based Premature Termination Implicit: Comparative Study in Contract Theory - Abed Ali, Jaafer; Abdul-Saheb, Ali (Journal of Legal Sciences, 2023)
For the premature termination of the contract is the creditor’s ability to request the termination of the contract due to the debtor’s breach of the execution date based on the debtor’s explicitness not to perform upon the occurrence of this date or because of a presumption proving that breach. Or return it to the extent of the creditor’s ability to prove what he claims, and thus the burden of proof falls on the creditor. There is no difficulty in proving the debtor’s declaration of non-performance, but the difficulty lies in proving the perceived breach in the future, that is, the creditor concludes earlier on the date of implementation that the debtor will breach his obligation and therefore the creditor does not obtain the implementation that he wanted from the contract, based on In this, there is a set of clues, emirates, and facts that reveal that the contractor will refrain from implementing an important aspect of his obligations when they are due.